THE IMPACT OF SHARIA COMPLIANCE AND SERVICE QUALITY ON CUSTOMER LOYALTY: THE MEDIATING ROLE OF DIGITAL BANKING SERVICES - Hana, Kharis Fadlullah; Safitri, Sefira Uzha; Sugianto, Sugianto (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study investigates the effects of sharia compliance and service quality on customer loyalty, with a focus on the mediating role of digital banking services. A quantitative research approach was employed using Partial Least Squares Structural Equation Modeling (SEM-PLS) for data analysis. Data were collected from 206 valid respondents, Generation Z users of Bank Syariah Indonesia (BSI) Mobile, out of 300 distributed questionnaires. The findings reveal that sharia compliance does not have a direct impact on customer loyalty but exerts an indirect influence through the use of BSI Mobile services. This is supported by the dominant response indicating that BSI Mobile facilitates the distribution of zakat, infaq, and shodaqoh. However, other findings show that many respondents remain uncertain about BSI’s business activities, leading to doubts about its adherence to halal practices and avoidance of usury (riba). In terms of service quality, BSI has delivered services as promised, and digital banking has enhanced customer convenience by enabling remote interaction with the bank. The study concludes that sharia compliance, in the absence of tangible evidence, does not directly influence customer loyalty. It is recommended that Sharia-compliant banks increase public education and outreach regarding the benefits of their business operations and ensure that sharia principles are more visibly implemented through digital banking services.